Evaluation of C-Reactive Protein and High Resolution Computed Tomography Scan Score to Initiate Early Steroid Therapy in Patients with COVID-19 Infection - Namirah Iftikhar; Muhammad Osama Rehman Khalid; Asif Husain Osmani; Gulraiz Hikmatyar; Sara Anjum Fazal (Pakistan Journal of Medicine and Dentistry)
Background: The severity of COVID pneumonia depends on the degree of lung parenchyma inflammation. This study aimed to identify prognostic factors for COVID-19 and examines the relationship between CRP levels and computed tomography Severity Scores (CTSS).